2009
DOI: 10.1088/0004-6256/138/1/295
|View full text |Cite
|
Sign up to set email alerts
|

H I Observations of Five Groups of Galaxies

Abstract: We present the results of H i observations of five groups of galaxies spanning a range of velocity dispersion and spiral fraction (brightest optical group member in parenthesis): NGC 7582 (NGC 7552), USGC U207 (NGC 2759), USGC U070 (NGC 664), USGC U412 (NGC 3822), USGC U451 (NGC 4065). Neutral intragroup gas is detected in three of the five groups. We present the discovery of a previously uncataloged galaxy in the USGC U070 group at α(2000) = 01 h 45 m 27 s , δ(2000) = +0436 19 , which we are designating FSW J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 46 publications
8
58
0
Order By: Relevance
“…Prior evidence for preprocessing of the gas content in the group environment comes from estimates of the H I mass function (HIMF) which historically have been derived from individual groups or small group samples (e.g. Verheijen et al 2000;de Blok et al 2002;Kovac et al 2005;Freeland et al 2009;Kilborn et al 2009;Pisano et al 2011;Hess 2011). Despite the small number statistics, calculations of the group HIMF reliably suggest a flatter slope at the low mass end than the field or global HIMF.…”
Section: Halo Occupation Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior evidence for preprocessing of the gas content in the group environment comes from estimates of the H I mass function (HIMF) which historically have been derived from individual groups or small group samples (e.g. Verheijen et al 2000;de Blok et al 2002;Kovac et al 2005;Freeland et al 2009;Kilborn et al 2009;Pisano et al 2011;Hess 2011). Despite the small number statistics, calculations of the group HIMF reliably suggest a flatter slope at the low mass end than the field or global HIMF.…”
Section: Halo Occupation Distributionmentioning
confidence: 99%
“…While Freeland et al (2009) found that groups with a mix of morphological types exhibit more signs of recent tidal interactions than groups dominated by one morphological type. Thus, collectively and over varying timescales, gravitational and to a lesser extent, hydrodynamical interactions can also transform galaxies from blue, star-forming, gas rich objects to red, passively evolving, gas poor objects in groups.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Image showing contours of neutral hydrogen gas with grayscale being optical observations from the Digitized Sky Survey. This is one group as determined by the FoF method but could be broken into two groups [3].…”
Section: Current Group Finding Techniquesmentioning
confidence: 99%